Early supported hospital discharge for foot disease: a co-design study - Rebecca Jessup; Samantha Hanna; Jaspreet Kaur; Iman Bayat; Cassandra Bramston (BMC, 2021)
Abstract Background There are more than 10,000 admissions each year in Australia for foot disease, with an average length of hospital stay of 26 days. Early supported discharge (ESD) has been shown to improve patient satisfaction and reduce length of stay without increasing the risk of 30-day readmissions. This research aims to gain consensus on an optimal model of early supported discharge for foot disease. Methods Three focus groups were held where preliminary components for an early discharge model, as well as inclusion and exclusion criteria, were identified with a purposefully sampled group of medical, nursing, allied health staff and consumers. Two researchers independently systematically coded focus group transcripts to identify components of an ESD model using an iterative constant comparative method. These components then formed the basis of a three phase Delphi study, with all individuals from the focus groups were invited to act as panellists. Panellists rated components for their importance with consensus established as a rating of either essential or very important by ≥80% of the panel. Results Twenty-nine experts (including 5 consumers) participated across the two study phases. Twenty-three (3 consumers) participated in the focus groups in phase one. Twenty-eight of the twenty-nine experts participated in the phase 2 Delphi. 21/28 completed round 1 of the Delphi (75% response rate), 22/28 completed round 2 (79% response rate), and 16/22 completed round 3 (72% response rate). Consensus was achieved for 17 (29%) of 58 components. These included changes to the way patients are managed on wards (both location and timeliness of care by the multidisciplinary team) and the addition of new workforce roles to improve co-ordination and management of the patients once they are at home. Conclusions A model of early supported discharge that would allow individuals to return home earlier in a way that is safe, acceptable, and feasible may result in improving patient satisfaction while reducing health system burden. Future trial and implementation of the ESD model identified in this study has the potential to make a significant contribution to the experience of care for patients and to the sustainability of the health system.